ANALISIS YURIDIS JASA TITIP DALAM PERDAGANGAN ANTAR NEGARA YANG MEMPENGARUHI DEVISA NEGARA INDONESIA DALAM KERANGKA MASYARAKAT EKONOMI ASEAN - Windy Aprila; Zulfikar Jayakusuma; Adi Tiara Putri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2021)
Currently there is an interesting phenomenon related to online business opportunities, namely titip service business (jastip). Jastip offers help to people who need or want to buy something but can't go where they want to. There is a deposit service fee when entering the territory of Indonesia. From the background of the problem, the formulation of the problem was born, namely, first how is the juridical analysis of titip services in trade between countries that affect the foreign exchange of The Indonesian state within the framework of the ASEAN Economic Community, Second, What countermeasures has the Indonesian government done in tackling splitting mode in titip service activities, The purpose of this writing is to know the juridical analysis of deposit services in trade between countries that affect the foreign exchange of The Indonesian state within the framework of the ASEAN Economic Community and to know the countermeasures that have been done by the Indonesian government in tackling splitting mode in the implementation of titip services. This type of research can be classified as normative-juridical research where this research is conducted on legal principles that point to the rejection of certain areas of legal system, by conducting advance identification of the legal methods that have been formulated in certain legislation. In this study, the data source used is secondary data with primary, secondary, and tertier legal materials conducted by means of literature studies. From the results of the research obtained that, first, the juridical analysis of titip services in trade between countries that affect the foreign exchange of the country in the framework of the ASEAN Economic Community, namely the increasing activity of titip services between these countries will lead to a decrease in foreign exchange in Indonesia, the law governing titip services in detail is not contained in the rules in Indonesia. This is because titip services can be done commercially or not. Titip services provide stimulus to imports within the framework of the ASEAN Economic Community, secondly, the countermeasures that have been done by the Indonesian government in tackling splitting mode in titip service activities, namely by cooperating with merchant associations and collecting information from the public, Checking Goods On Customs Custom on Passengers who cheat, Checking Purchase Documents, and anti splitting.Keywords : Jasa Titip-Perdagangan-MEA